METHODS OF DETERMINING THE MEANING OF A WORD IN CONTEXT IN TRANSLATION (Scientific journal of the Fergana State University, 2024)
This article shows three methods of studying the meanings of words – reference theory, component analysis and postulates of meaning based on the analysis of different examples. In the process of translation, the fact that the translator does not understand the meaning of the word in the context of the original language, but the meaning of the word itself, causes problems such as the wrong translation of this word in the translation. It is this research that helps to overcome such a problem. The following results are presented in the research: reference theory cannot give the full meaning of the word, it is used together with the component analysis, the two analysis methods cannot give the meaning of the word in the context.The third - the method of analysis of meaning forms can determine the pragmatic and semantic features of the word, and this is convenient for the translator.